Problems of Linguistic Ecology in Media and Online Information Spaces - Omarbekova, Gulnara Abildayevna; Baiteliyeva, Zhanar Daribekovna; Nurgaliyeva, Dolores Abildayevna; Donbayeva, Ainur Beketovna (Forum for Linguistic Studies, 2025)
This study focuses on the analysis of invective means increasingly used in the language of contemporary newspapers and magazines within the media space. The transformations taking place in the language of mass media are closely linked to the broader changes in the world and culture under the influence of digital culture and globalization. These transformations primarily concern communicative processes in the media sphere, which have evolved from mere acts of transmitting and receiving information into mechanisms that determine the nature of social interaction, ranging from manipulative to benevolent. An examination of media discourse reveals a growing prevalence of negative linguistic phenomena associated with verbal aggression directed at the audience. The aim of the study is therefore to identify and describe the essence of invective linguistic means, to classify them into distinct groups, to distinguish them from non-normative vocabulary, and to consider the role of juridical linguistics and media ecology in preventing linguistic violence in interpersonal and virtual communication. The research employs empirical methods (associative and sociolinguistic experiments) and theoretical methods (lexico-stylistic, lexico-semantic, communicative-pragmatic, and corrective analyses). The study produced several key results: the notion of invective linguistic means is defined; their classification is outlined; distinguishing features separating invective from non-normative vocabulary are identified; the legal foundations of uncontrolled use of invective means are analyzed; and attention is drawn to the necessity, from a media-ecolinguistic perspective, of protecting the communicative space of mass media from the use of invective expressions that cause harm to the addressee.